Postoperative complications and unanticipated healthcare encounters following mini-laparotomy vs. laparoscopic/robotic-assisted sacrocolpopexy: a comparative retrospective study - Henry H. Chill; Alireza Hadizadeh; Claudia Paya-Ten; Angela Leffelman; Cecilia Chang; Nani P. Moss; Roger P. Goldberg (BMC, 2024)
Abstract Background Pelvic organ prolapse is a debilitating condition impacting lives of millions of women worldwide. Sacrocolpopexy (SCP) is considered an effective and durable surgical technique for treatment of apical prolapse. The aim of this study was to compare short-term outcomes including postoperative complications and unanticipated healthcare encounters between patients who underwent SCP with a mini-laparotomy approach compared to patients treated with laparoscopic and robotic-assisted laparoscopic SCP. Methods This was a retrospective cohort study including patients treated for apical prolapse at a university affiliated urogynecology practice. Patients over the age of 18 who underwent abdominal SCP between 2019 and 2023 were included. The cohort was formed into two groups: (1) Patients who underwent SCP through a mini-laparotomy incision (Mini-lap group); (2) Patients who underwent laparoscopic or robotic-assisted laparoscopic SCP (Lap/Robot group). Results A total of 116 patients were included in the final analysis. Ninety patients underwent either laparoscopic or robotic-assisted SCP, whereas 26 patients underwent SCP with a mini-laparotomy approach. Study participants exhibited a mean age of 63.1 ± 10.3 years, mean body mass index (BMI) of 25.8 ± 4.9 Kg/m2, and 77.6% of them identified as Caucasian. Upon comparison of demographic and past medical history between groups there were no statistically significant differences in age, BMI, menopausal status, race, parity or comorbid conditions. Patients in the Mini-lap group were less likely to have undergone previous abdominal surgery (11.5% vs. 50.6%, p < 0.001) and had more severe apical prolapse (stage 4 prolapse, 40% vs. 21.2%, p < 0.001) than their counterparts in the Lap/robot group. Regarding intraoperative parameters, length of surgery was significantly shorter in the Mini-lap group compared to the Lap/robot group (97.3 ± 35.0 min vs. 242.0 ± 52.6 min, p < 0.001). When focusing on the primary outcome, postoperative complications within the first 30 days after surgery, there were no differences noted between groups. Additionally, the number of unanticipated healthcare encounters, such as phone calls, clinic visits, emergency department visits, urgent care visits, readmissions and reoperations were similar between groups. Conclusions Mini-laparotomy approach for SCP is safe with comparable intra- and postoperative complications, and unanticipated healthcare encounters compared to conventional minimally invasive methods.